Sapaan dalam Bahasa Dayak Ketungau Sesat: Kajian Sosiolinguistik - Pabianus Simon; Suardi Suardi (Mandalika Journal of Business and Management Studies, 2026)
This study focuses on greetings in the Dayak Ketungau Sesat language. The greetings in question are based on blood relations and marriage relations. The method used in this study is descriptive. The data in this study are greetings in the BDKS obtained from informants. The data were collected using note-taking and recording techniques. Based on the results of the study, the researchers managed to collect 20 greetings based on blood relations and 11 greetings based on marriage relations.